2016
DOI: 10.1016/j.jaad.2015.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary melanoma: Update on syndromes and management

Abstract: Malignant melanoma is considered the most lethal skin cancer if not detected and treated at its early stages. About 10% of melanoma patients report a family history of melanoma; however, individuals with features of true hereditary melanoma (i.e. unilateral lineage, multi-generational, multiple primary lesions, and early onset of disease) are in fact quite rare. Although many new loci have been implicated in hereditary melanoma, CDKN2A mutations remain the most common. Familial melanoma in the presence of mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
80
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(88 citation statements)
references
References 68 publications
(85 reference statements)
0
80
1
Order By: Relevance
“…However, an adolescent twin study from the UK found no evidence for D9S942 as a quantitative-trait locus influencing nevus density (Barrett et al , 2003) and a familial-based investigation of a potentially nevogenic variant (A148T) near D9S942 also found no association with common acquired nevus counts (Bertram et al , 2002). Germline mutations in CDKN2A are strongly associated with FAMMM syndrome, and individual members of these families often have abundant numbers of atypical and common nevi (Gruis et al , 1995; Hussussian et al , 1994; Soura et al , 2016). However, not all individuals with CDKN2A mutations present with excessive or even higher nevus counts.…”
Section: Discussionmentioning
confidence: 99%
“…However, an adolescent twin study from the UK found no evidence for D9S942 as a quantitative-trait locus influencing nevus density (Barrett et al , 2003) and a familial-based investigation of a potentially nevogenic variant (A148T) near D9S942 also found no association with common acquired nevus counts (Bertram et al , 2002). Germline mutations in CDKN2A are strongly associated with FAMMM syndrome, and individual members of these families often have abundant numbers of atypical and common nevi (Gruis et al , 1995; Hussussian et al , 1994; Soura et al , 2016). However, not all individuals with CDKN2A mutations present with excessive or even higher nevus counts.…”
Section: Discussionmentioning
confidence: 99%
“…Around 20-40% of people with familial melanoma worldwide have a germline mutation in the CDKN2A gene, whereas germline mutations in another gene, CDK4, are seen in only about 1% of melanoma-prone families [20]. FAMMM should be considered in people with multiple nevi (more than 50), history of cutaneous melanoma in first and second-degree relatives with early onset or a family history of melanoma, pancreatic cancer and astrocytoma [20,21].…”
Section: Familial Atypical Multiple Mole Melanomamentioning
confidence: 99%
“…occurs more frequent in patients with FAMMM syndrome (familial or sporadic form) or hereditary melanoma [1,2]. About 10% of all melanoma patients report a family history of melanoma; however, individuals with features of true hereditary melanoma (ie, unilateral lineage, multigenerational, multiple primary lesions, and early onset of disease) are in fact quite rare [1]. Although many new loci have been implicated in hereditary melanoma, CDKN2A mutations remain the most common [1].…”
Section: Descriptionmentioning
confidence: 99%
“…primary melanomas and internal organ malignancies, especially pancreatic cancer; therefore, a multidisciplinary approach is necessary in many cases [1]. The value of dermoscopic examination and total body photography performed at regular intervals has been suggested by a number of studies, and should therefore be considered for these patients and their first-degree relatives [1,2].…”
mentioning
confidence: 99%
See 1 more Smart Citation